LEXICAL-SYNTACTIC STYLISTIC DEVICES: SIMILE, PERIPHRASIS, LITOTES, GRADATION - Ochilova Ziyoda; Joʻrayev Ziyodbek (TADQIQOTLAR, 2025)
Annotation This article discusses four important lexical-syntactic stylistic devices: simile, periphrasis, litotes, and gradation. It explains their definitions, examples, and functions, highlighting how they enrich speech and writing. The article emphasizes the role of these devices in creating vividness, emotional coloring, and stylistic variety.